DAMPAK PENYESUAIAN LAJUR KHUSUS KENDARAAN BERAT TERHADAP KINERJA LALU LINTAS - Hasudungan, Jose Isai; Adwitiya, R. Ivan; Purnomo, Robby Yudo; Kusuma, Andyka (Jurnal Transportasi, 2023)
Traffic performance on the Narogong highway has problems with the desired speed of the highway, as a result of the large number of heavy vehicles that pass through the Narogong Highway, this study was conducted to see that moving heavy vehicles to the left lane can have a positive impact on road traffic performance. observed. Data processing uses microscopic simulations to get the desired road simulation, from this simulation calibration and validation are carried out first to get the existing simulation conditions similar to the observed conditions of the road section being reviewed. From the results of the existing conditions that have been validated, a simulation of the design road model is carried out to see if there are changes that affect the design made by the author. Based on the simulation results, it was found that moving heavy vehicles to the left lane had an impact on increasing the speed of other vehicles such as motorcycles and cars significantly. Therefore, it is necessary to add new policies about heavy vehicle. ABSTRAK Kinerja lalu lintas di jalan raya Narogong memiliki permasalahan dengan kecepatan yang diinginkan dari jalan raya tersebut, akibat dari banyaknya kendaraan berat yang melewati ruas jalan raya Narogong, Penelitian ini dilakukan untuk melihat pemindahan kendaraan berat ke lajur kiri dapat berdampak positif pada kinerja lalu lintas ruas jalan yang diamati. Pengolahan data menggunakan simulasi mikroskopis untuk mendapatkan simulasi jalan yang diinginkan, dari simulasi ini dilakukan kalibrasi dan validasi terlebih dahulu untuk mendapatkan kondisi simulasi eksisting yang mirip dengan kondisi observasi ruas jalan yang ditinjau. Dari hasil kondisi eksisting yang sudah divalidasi, dilakukan simulasi model jalan desain untuk melihat apakah ada perubahan yang berpengaruh dari desain yang dilakukan oleh penulis. Berdasarkan hasil simulasi ditemukan bahwa pemindahan kendaraan berat ke lajur sebelah kiri berdampak pada peningkatan kecepatan kendaraan lain seperti motor dan mobil secara signifikan, sehingga diperlukannya kebijakan yang baru untuk kendaraan berat.